Nove tehnologije sustava obavješćivanja u prometu - Kos, Vesna; Kovačević, Dražen (Promet - Traffic&Transportation, 2012)
The paper deals with traditional means of information in traffic as well as modern systems as additions to traditional methods. The paper discusses the advantages and disadvantages of new information system technologies and the needs of transport companies in the future.